Management Of Bank Indonesia: Social Programs At Darul Islah - Afrianto, Afrianto; Pahrudin, Agus; Fauzan, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2023)
With the spirit of Dedication to the Country, Bank Indonesia will always be present in every sense of Indonesia, and provide the best service to realize a just, prosperous and prosperous Indonesian society. What Bank Indonesia does is a reflection of how a company also has the responsibility to give rights to others, in this case pesantren where people with religious and nationalist characters are printed. By distributing this social assistance, including the provision of infaq. At Darul Islah Tulang Bawang Islamic Boarding School, the Bank Indonesia Social Assistance Program (PBSI) is realized in the form of a green house project used as a place for intanon melon cultivation from the Netherlands. The formulation of the problem in this study is, first, how to plan the Bank Indonesia Social Assistance Program (PBSI) at Darul Islah Tulang Bawang Islamic Boarding School. Second, how to implement the Bank Indonesia Social Assistance Program.